A non‐European European Union. (4th February 2022) - Harb, Siba
Abstract: The European Union (EU) is a union among some of the wealthiest and most powerful states in the world. It is desirable to become part of it; indeed, many states would want to be part of it. However, only a handful of states are eligible to be considered for membership. We are normally wary of unions of powerful individuals that exclude less powerful individuals. And we ought to have concerns about the permissibility of having an exclusive union like the EU. Yet, and to the best of my knowledge, its status as an exclusive union has not been subject to question, certainly not in the philosophical literature on EU justice. In this paper, I focus on the legitimacy of one particular EU exclusion rule: For a state to be eligible for membership it must be European. I argue that this criterion is illegitimate.